The Identification of Language Functions Based on Halliday’s Framework on Buleleng Regency Tourism Office Social Media - Satwika, Ida Bagus Wiswanatha; Sari, Rima Andriani; Adnyani, Ni Luh Putu Sri (PEMA, 2025)
This study aims to analyze the language functions in the posts of the Buleleng Regency Tourism Office on Instagram @visit.northbali to determine the linguistic functions used in digital tourism promotion. This study uses a qualitative descriptive method with content analysis techniques on posts from January to June 2025. The data were analyzed based on the seven functions of language according to M.A.K. Halliday, namely instrumental, regulatory, interactional, personal, informative, heuristic, and imaginative. The results showed that all functions of language were found, with the informative, instrumental, and imaginative functions dominating, while the regulatory, interactional, personal, and heuristic functions appeared less frequently. The informative function was used to convey clear information about destinations, the instrumental and regulatory functions to encourage audience action, and the personal and imaginative functions to build emotional closeness and a positive image. These findings indicate that the Buleleng Regency Tourism Office strategically combines various language functions to increase the effectiveness of messages and audience engagement in digital tourism promotion.